"The Burden of Pregnancy"; heavier for the heaviest? The changes in Health Related Quality of Life (HRQoL) assessed by the 15D instrument during pregnancy and postpartum in different body mass index groups: a longitudinal survey. (12th January 2017) - Sahrakorpi, Niina; Koivusalo, Saila B.; Stach‐Lempinen, Beata; Eriksson, Johan G.; Kautiainen, Hannu; Roine, Risto P.
Abstract: Introduction: Only little information is available on health‐related quality of life (HRQoL) and its changes during the course of a normal pregnancy. We studied changes in HRQoL in a pregnant population during pregnancy and until 1 year postpartum in different body mass index (BMI) groups. Material and methods: Seven hundred and fifty pregnant women attending the first ultrasound examination before gestational week 14 were invited to participate in a longitudinal, communal‐based survey. The participants were divided into three groups according to their BMI; <25, 25–29.9, and ≥30 kg/m 2 . The women were asked to fill in questionnaires assessing HRQoL (15D), depressive symptoms (Edinburgh Depression Scale, EPDS), medical, obstetric and socioeconomic status at baseline. HRQoL and EPDS were re‐assessed at 30 weeks of gestation, and 6 weeks, 3 and 12 months postpartum. Results: Of the invited 750 mothers, 325 (43%) returned the questionnaires and at least one follow‐up questionnaire. At baseline, mean 15D scores decreased with increasing BMI but the difference was not statistically significant when adjusted for age, educational attainment, parity or EPDS‐scores (0.929, 0.921 and 0.916, p = 0.16). During the course of pregnancy, the HRQoL of all women decreased but this decrease was significantly greater in the obese group (−0.088; 95% CI −0.110 to −0.065) than in the other groups [−0.054 (95% CI −0.062 to −0.045) and −0.051 (95% CI −0.068 to −0.033), p = 0.019]. Within 3 months postpartum the mean HRQoL recovered in all BMI groups to baseline levels, irrespective of the mode of delivery or pregnancy‐related complications. Conclusion: The burden of pregnancy is heavier for the heaviest.